Fano resonant optical coatings platform for full gamut and high purity structural colors - ElKabbash, Mohamed; Hoffman, Nathaniel; Lininger, Andrew R.; Jalil, Sohail A.; Letsou, Theodore; Hinczewski, Michael; Strangi, Giuseppe; Guo, Chunlei (Nature communications, 2023)
Structural coloring is a photostable and environmentally friendly coloring approach that harnesses optical interference and nanophotonic resonances to obtain colors with a range of applications including display technologies, colorful solar panels, steganography, décor, data storage, and anticounterfeiting measures. We show that optical coatings exhibiting the photonic Fano Resonance present an ideal platform for structural coloring; they provide full color access, high color purity, high brightness, controlled iridescence, and scalable manufacturing. We show that an additional oxide film deposited on Fano resonant optical coatings (FROCs) increases the color purity (up to 99%) and color gamut coverage range of FROCs to 61% of the CIE color space. For wide-area structural coloring applications, FROCs have a significant advantage over existing structural coloring schemes. Fano resonant optical coatings (FROCs) present an ideal platform for structural coloring from thin-film metamaterials. This platform provides full-color gamut coverage at greater than 61% of the CIE gamut, with exceptionally high purity (up to 99%) and high brightness. FROCs exhibit tunable iridescence, cost-effective and scalable manufacturing, and significant advantages over existing structural coloring schemes.